Thermokarst processes increase the supply of stabilizing surfaces and elements (Fe, Mn, Al, and Ca) for mineral–organic carbon interactions - Monhonval, Arthur; Strauss, Jens; Thomas, Maxime; Hirst, Catherine; Titeux, Hugues; Louis, Justin; Gilliot, Alexia; du Bois d'Aische, Eléonore; Pereira, Benoît; Vandeuren, Aubry; Grosse, Guido; Schirrmeister, Lutz; et al. (Permafrost and Periglacial Processes, 2022)
The stabilizing properties of mineral-organic carbon interactions have been studied in many soil environments (temperate soils, podzol lateritic soils, paddy soils). Recently, interest in their role in permafrost regions is increasing as permafrost was identified as a hotspot of change. In thawing ice-rich permafrost regions, such as the Yedoma domain, 327-466 Gt of frozen organic carbon (OC) is buried in deep sediments. Interactions between minerals and OC are important since the OC is located in close contact with the mineral matrix. Mineral surfaces and elements could mitigate recent and future greenhouse gas emissions through physical and/or physico-chemical protection of OC. The dynamic changes of redox and pH conditions associated with thermokarst lake formation and drainage, trigger metal-oxide dissolution and precipitation, likely influencing OC stabilization and microbial mineralization. However, the influence of thermokarst processes on mineral-OC interactions remains poorly constrained. In this study, we aim to characterize Fe, Mn, Al and Ca minerals and their potential protective role for OC. Total and selective extractions were used to assess the crystalline and amorphous oxides or complexed metal pools as well as the organic acids found within these pools. We analyzed four sediment cores from an ice-rich permafrost area in Central Yakutia, which were drilled i) in undisturbed Yedoma uplands, ii) beneath a recent lake formed within Yedoma deposits, iii) in a drained thermokarst lake basin, and iv) beneath a mature thermokarst lake from the early Holocene period. We find a decrease in the amount of reactive Fe, Mn, Al and Ca in the deposits upon lake formation (promoting reduction reactions), and this was largely balanced by an increase in the amount of reactive metals in the deposits upon lake drainage (promoting oxidation reactions). We demonstrate an increase in the metal:C molar ratio upon thermokarst process, which may indicate an increase of metal-C bindings and could provide a higher ...